INVESTIGATING THE EFFICACY OF PEER TUTORING TECHNIQUE IN IMPROVING STUDENTS’ SPEAKING ABILITY IN SMA ULIL ALBAB EAST LOMBOK - Jupri Jupri; Lalu Budi Karyawan (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
This study was meant to find out the Efficacy of Peer Tutoring Technique in Improving Students’ Speaking Ability. Pursuant to the researcher’s pretest and teaching experience, it was found that students speaking ability was low. It was considered necessary for the researcher to conduct action research since this school is the researcher’s institution. This study was conducted in action research (PTK). The setting of the study was SMA Ulil Albab East Lombok involving 25 students as the participants of the research. The instruments of the research were test and observation sheets. The criterion of success was KKM in which KKM for East Lombok is 70. The data were analyzed by assessing the criterion of success and also the statistical computation in which the researcher calculated the result of descriptive and inferential statistics. The descriptive statistical analysis shows that the mean scores of the posttest is higher than the pretest, resulting in 83.4 < 70.6. Therefore, the peer-tutoring technique can improve the students’ speaking ability in SMA Ulil Albab, East Lombok, West Nusa Tenggara Province. The sig. (2-tailed) is 0.000 which is lower than the significant level (0.05). Therefore, the peer tutoring technique can improve the students’ speaking ability in SMA Ulil Albab, East Lombok, West Nusa Tenggara Province. The result of the t-test is higher than the t-table, 7.67 < 1.70. This concludes that there is significant different in the teaching of speaking by using peer tutoring technique in improving the students’ speaking ability. The total number of students who were considered as active in involving themselves in the teaching and learning activities has met the criterion of success. It was proven by the percentages of the very active students (56%), supported by the percentage of the active students (32%) achieved 88% which was more 18% than the percentage of criteria of success which was 70%. The result of the posttest shows almost all students got score higher than 70. It means that more than 70% of the students got score 70 or higher. This surely proves that the criterion of success has been met. The teaching of speaking by using peer tutoring technique can help the student’s achievement in improving speaking ability[v1] .  [v1]Abstract must in English and Indonesian Version